Antioxidant and antiacetylcholinesterase activities of Pluchea indica Less - Ab. Rahim, Noridayu; Hii, Yueh Feng; Abas, Faridah; Shaari, Khozirah; Lajis, Nordin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
This study was undertaken to evaluate the antioxidant and acetylcholinesterase inhibition properties of stems and leaf of hexane and methanolic extracts of Pluchea indica. Methanolic extract of leaves showed the highest antioxidant activity (IC50= 24.45 ± 0.34 μg/ml) and total phenolic contents (573.52 ± 6.2 mg GAE/100 g crude extract), in DPPH radical scavenging and Folin-Ciocalteu assays respectively, however, it failed to inhibit acetylcholinesterase in TLC bioautographic detection. The rest of plant extracts, included methanolic extract of stems, hexane extract of both leaves and stems, were detected to have acetylcholinesterase inhibitory properties. Hexane extract of both leaves and stems exhibited lower or negligible level of antioxidant activity and phenolic contents. Pluchea indica may provide a potential natural source of bioactive compounds, and maybe beneficial to the human health.